Marriage in the Age of Advancement of Digital Technology: Study of Nahdlatul Ulama and Muhammadiyah Fatwa on the Legality of Marriage via Online - Wajidi, Farid; Mustafid, Fuad (Program Studi Hukum Keluarga Islam, 2023)
The phenomenon of online marriage contracts is starting to emerge and this raises issues regarding its validity. Majelis Tarjih dan Tajdid Muhammadiyah and Bahtsul Masail Nahdlatul Ulama have responded and issued fatwas related to this issue with different legal conclusions. This article examines and explains the causes of differences in fatwas and at the same time arguments issued by Muhammadiyah and Nahdlatul Ulama regarding the law of online marriage contracts. Using the usul fiqh approach, this article finds two findings. First, there is a difference in fatwas between Muhammadiyah and Nahdlatul Ulama due to differences in the legal istinbath method; Muhammadiyah uses the burhani method, while Nahdlatul Ulama uses the qauli method. Second, Muhammadiyah interprets the concept of ittihad majelis as a continuity of time between ijab and qabul, while Nahdlatul Ulama interprets it as a unitary place and not merely a unitary speech. This has implications for the legal status of online marriage contracts. Muhammadiyah considers online marriage contracts via online as a valid contract, while Nahdlatul Ulama considers it invalid.